The relationship between learning outcomes and motivation for learning to write using indonesian against student management - Zulaika Zulaika; Happy Fitria; Syaiful Eddy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to analyze and describe: 1) the relationship between learning outcomes and student management, 2) the relationship between the motivation to learn to write in Indonesian and student management, 3) the relationship between learning outcomes and motivation to learn to write using Indonesian language against student management. The results of the study stated: 1) there is a relationship between Learning Outcomes and Student Management; 2) there is a relationship between the Motivation of Learning to Write Using Indonesian and Student Management; and 3) there is a relationship between Learning Outcomes and Learning Motivation on Student Management at Sekolah Dasar Negeri Kecamatan Jirak Jaya.